Experimental investigation on the drop-in performance of R407C as a substitute for R22 in a screw chiller with shell-and-tube heat exchangers - Lee, DY; Ahn, Y; Kim, Y; Kim, Y; Chang, YS; Nam, L (ELSEVIER SCI LTD, 2002)
A drop-in test of a mixed refrigerant R407C is performed in a commercial screw chiller with shell-and-tube heat exchangers originally designed for R22. The test results show a severe performance reduction when substituting the refrigerant from R22 to R407C. The reason for the performance reduction is analyzed comprehensively, and the influence of thermodynamic properties, compressor efficiency, and heat transfer is evaluated quantitatively. The major factor causing the performance reduction is assessed as the degradation of the heat transfer in using the mixed refrigerant, R407C. The heat transfer degradation in the evaporator is found to be larger and influences more on the chiller performance reduction. The performance reduction caused by the evaporator is approximately two times compared with that of the condenser. (C) 2002 Elsevier Science Ltd and IIR. All rights reserved.
Keywords: REFRIGERANT MIXTURES; ALTERNATIVES; EVAPORATION; R-22; PURE